Fixed combination of oral NEPA (netupitant‐palonosetron) for the prevention of acute and delayed chemotherapy‐induced nausea and vomiting in patients receiving multiple cycles of chemotherapy: efficacy data from 2 randomized, double‐blind phase III studies - Schwartzberg, Lee; Jordan, Karin (Cancer medicine, 2019)
The efficacy of oral NEPA (netupitant‐palonosetron 300/0.50 mg) was evaluated from two randomized phase III studies in patients receiving HEC, AC, or MEC over multiple chemotherapy cycles. Oral NEPA ...
Gesehen am 25.11.2019